2016
DOI: 10.5433/1679-0359.2016v37n4supl1p2609
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic of nitrogen and chemical analysis of deferred grazing marandu palisadegrass fertilized with urea and poultry litter

Abstract: This study aimed to evaluate and quantify the methodology of stable isotopes, 15 N values for the organic fertilizer (chicken manure) and inorganic (urea). In addition to evaluating the incorporation rate, chemical half-life and analysis thereof, for possible traceability through the pasture fertilized with different sources of N. The technique of employment with use of tracer stable isotope 15 N possible to estimate the changes in the N soil, even in the face of the various changes that take place concurrent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Other studies indicated that the use of litter in agriculture added chemical elements that could improve chemical, physical, and biological attributes of the soil (ARRUDA et al, 2014;SILVEIRA JÚNIOR et al, 2015;LIMA et al, 2016;OLIVEIRA et al, 2016). Arruda et al (2014) evaluated the effect of poultry litter in substitution for chemical fertilizers on elephant grass pasture in Botucatu, São Paulo, and observed that regardless of the application form -single or split dose -the litter used as nitrogen fertilizer replaced urea in the cover fertilization of elephant grass.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies indicated that the use of litter in agriculture added chemical elements that could improve chemical, physical, and biological attributes of the soil (ARRUDA et al, 2014;SILVEIRA JÚNIOR et al, 2015;LIMA et al, 2016;OLIVEIRA et al, 2016). Arruda et al (2014) evaluated the effect of poultry litter in substitution for chemical fertilizers on elephant grass pasture in Botucatu, São Paulo, and observed that regardless of the application form -single or split dose -the litter used as nitrogen fertilizer replaced urea in the cover fertilization of elephant grass.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, knowledge of this value is important in the calculation of nutrient replacement required by crops. In the present study, the dry matter content was 43.32%, below the value of 87% obtained by Lima et al (2016).…”
Section: Fertilizer Characteristicsmentioning
confidence: 92%
“…Poultry litter has important concentrations of nitrogen, phosphorus, potassium, and micro minerals such as copper and zinc (Oviedo-Rondon, 2008;Lima et al, 2016). According to Costa et al (2015), there is a necessity for studies on the use of poultry litter as organic fertilizer in the productivity of cultures.…”
Section: Introductionmentioning
confidence: 99%